2014
DOI: 10.17350/hjse19030000001
|View full text |Cite
|
Sign up to set email alerts
|

Porous metal-organic Cu(II) complex of L-Arginine; synthesis, characterization, hydrogen storage properties and molecular simulation calculations

Abstract: M ost known alternative to fossil fuel energy system is widely researched hydrogen economy in the other name hydrogen energy system [1]. The main obstacle to use hydrogen economy in daily life is to store hydrogen as an energy carrier, safely and economically [2][3]. In order to store hydrogen, compressed and liquid gas systems [4] have been being used but for safely and more profitable storage there are many choices such as, metal hydrides [5], carbon nanotubes [6][7], metal organic frameworks (MOFs) [8] whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…It was found that the previous arginine compound could been adsorbed approximately 0.8 wt. % hydrogen at 77 K and 1 bar pressure [28,29]. The value was 10 times bigger than the present work because the molecular spaces in the present work filled with the free and coordinated natrium and sulfite molecules.…”
Section: Hydrogen Adsorption Isotherms Of Arginine Complexcontrasting
confidence: 57%
See 1 more Smart Citation
“…It was found that the previous arginine compound could been adsorbed approximately 0.8 wt. % hydrogen at 77 K and 1 bar pressure [28,29]. The value was 10 times bigger than the present work because the molecular spaces in the present work filled with the free and coordinated natrium and sulfite molecules.…”
Section: Hydrogen Adsorption Isotherms Of Arginine Complexcontrasting
confidence: 57%
“…Monte Carlo calculations realized in different 10 fugacity steps by using Metropolis method within 10 000 equilibration and production steps at 77 K. In addition, the force field, which was modified for the low temperature intermolecular interaction because of the quantum effects, used in the adsorption calculations. The details of the force field modification and the parameters explained deeply in our previous work [28,29]. The simulated model validated with the experimental surface area calculations by using Amorpous Cell module.…”
Section: Hydrogen and Nitrogen Adsorption Calculationsmentioning
confidence: 63%
“…e value of Racah parameter B (free ion) is larger than that of B (complex) due to the covalence bonding of the complex. e value of β (nephelauxetic ratio) < 1 is calculated according to equation (1). β < 1, validating octahedral geometry [34,35].…”
Section: Uv-vis Absorption Spectramentioning
confidence: 99%
“…is class of molecules have been found throughout the life science and vary tremendously in their function and complexity. ese compounds play an essential part of metabolism and cellular signaling and as a part of drugs and as hydrogen storage media [1].…”
Section: Introductionmentioning
confidence: 99%
“…Some of previous investigations of arginine complexes focused on bands shifting of carbonyl stretching around 1700cm -1 and of imine stretching around 1550cm -1 (Kong and Yu 2007;Ozturk et al 2014;Wu et al 2010;and Sunatkari et al 2015) due to their interactions with metals.…”
Section: Introductionmentioning
confidence: 99%